MAKNA SITUS CAGAR BUDAYA SOKOLIMAN BAGI MASYARAKAT - Putri Novita Taniardi (BALAI ARKEOLOGI PAPUA, 2012)
Artifacts store messages from the past. An artifact is a reflection of human culture whose support the culture of using artifact. Similarly, artifacts found in Sokoliman’s Cultural Heritage which consist of megalithic objects. These artifacts have undergone a transformation; experienced manufacture, use, until the deposition. Today, these artifacts are in the midst of community and given a new meaning based on their own perspective. Giving meaning is closely related to the existence of sites community’s perspective. The meaning that given by community can be a reflection on the preservation of the site itself.